Characterization of high-power and very-high-power short-duration radiofrequency lesions performed with a new-generation catheter and a temperature-control ablation mode. (19th May 2022) - Lozano-Granero, C; Moreno Planas, J; Matia-Frances, R; Hernandez-Madrid, A; Sanchez-Perez, I; Zamorano Gomez, JL; Franco-Diez, E
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: High-power short-duration (HP-SD) and very high-power short-duration (VHP-SD) has recently emerged as an alternative ablation strategy to shorten application times while maintaining or improving the effectiveness and safety of atrial fibrillation ablation (1 - 2). Although usually performed with standard irrigated-tip catheters in a power-controlled mode, a novel dedicated catheter with a multi-thermocouple system capable of real-time temperature monitoring and optimized for temperature-controlled ablation by power and irrigation rate modulation has been developed for this scenario (3 - 4). Purpose: We conducted an experimental ex-vivo study to analyse the differences between radiofrequency lesions obtained with this novel catheter (QDOT MICRO®) using HP-SD and VHP-SD. Besides, we also aim to compare them to HP-SD lesions obtained with a standard non-dedicated catheter (THERMOCOOL SMARTTOUCH®) and to conventional-powered lesions performed with either catheter. Methods: 280 epicardial radiofrequency applications were performed on porcine left ventricle submerged in 37ºC saline: 40 VHP-SD (90W) with QDOT MICRO (4 sets of 10 using a contact force (CF) of 10 and 20 grams and an application time of 3 and 4 seconds); 80 HP-SD lesions (50W), 40 of them with QDOT MICRO and 40 of them with THERMOCOOL SMARTTOUCH (4 sets of 10 lesions using a CF of 10 and 20 and an ablation index (AI) of 400 and 550 with each catheter) and 160 conventional-power lesions (35 and 40W), 80 of them with QDOT MICRO and 80 of them with THERMOCOOL SMARTTOUCH (4 sets of 10 lesions using a CF of 10 and 20 and an AI of 400 and 550 for each catheter and power setting). After each application, lesions were cross-sectioned and measured. Volume vas calculated using a validated formula (5). Results: In an intracatheter analysis, HP-SD lesions were bigger than VHP-SD ones, both when using parameters intended for posterior wall ablation (AI 400 in HP-SD or 3 seconds in VHP-SD), 98.1±11.7 vs 36.8±8.5 mm3, p<0.0001 with 10g CF, and 106.7±8.1 vs 52.3±9.8 mm3, p<0.0001 with 20g CF; and when using parameters intended for anterior wall ablation (AI 550 in HP-SD or 4 seconds in VHP-SD), 227.6±25.1 vs 61.0±7.8 mm3, p<0.0001 with 10g CF, and 186.6±23.3 vs 72.2±5.0 mm3, p<0.0001 with 20g CF (see figure). In an intercatheter analysis, conventional as well as HP-SD lesions were generally smaller with THERMOCOOL SMARTTOUCH than with QDOT MICRO, although less difference could be found when applying a CF of 20g instead of 10g (see figure and table). Conclusions: VHP-SD lesions are smaller than HP-SD ones, which would allow for a safer and faster ablation. However, a HP-SD strategy would be preferable over VHP-SD if greater lesion volume is desirable.